Desain Sosial Brand Activation Komunitas Ciliwung Condet Melalui Media Virtual - Baskoro Suryo Banindro; M.Faizal Rochman; Lintang Andamari Hananto Soenarto (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2022)
This study aims to realize social design virtually through brand activation for the Ciliwung Condet Community (KCC) Jakarta. The urgency of this research is to obtain the ideal virtual design format and foundation in the social media format of the Instagram, Facebook and Website platforms related to the Ciliwung Condet Community. The data were collected based on field studies, interviews and extensive literature. This study uses a descriptive method with an analytical approach of What, Who, Why, When, Where and How (5W1H). The results of this study provide a conclusion that the format of field social research through Project Learn Based (PLB) and Project Case Study (PCS, can be used as a basis for solving problems and producing a branding design for the Ciliwung Condet Jakarta Area community, through virtual digital media.